PAKISTAN TUR-RETUR: Forhandlinger af hjem og tilhørsforhold inden for flergenerationsfamilien - Rytter, Mikkel (Tidsskriftet Antropologi, 2004)
This article inquires into the “homeland imaginary” of Pakistani who emigrated to Denmark during the past four decades. In addition to the search for economic prosperity, the generations of migrants have also created visions of the places they came from and their relations to the family members left behind. The “homeland imaginary” gives emphasis to the “good life” in the bosom of caring, extended families. Nostalgic yearning to revitalize such family values, considered lost in Denmark, motivates some individuals and families to return to Pakistan, where they, however, rarely find the good life or homeland they imagined. Based on narratives recounted by members of three Pakistani families who returned to Pakistan after living in Denmark, this paper discusses how patriarchal authority, as well as notions of home and identity, are negotiated within the extended family. The article then questions the conflation of popular and analytical representations of the close-knit extended family found in the ethnographic literature and outlines an analytical perspective of the extended family that includes multiple subject positions based on age, gender and civil status that sheds new light on the practices and visions of Pakistani family life.